PERBEDAAN KOMUNIKASI INTERPERSONAL ANTARA SISWA YANG MEMILIKI PACAR DENGAN SISWA YANG TIDAK MEMILIKI PACAR - Harahap, Juli Yanti (Aksara Public, 2018)
Good and quality communication can help improve relationships and overcome problems, whereas poor communication will disrupt those relationships and tends to lead to ongoing conflict. This study aims to determine whether there are differences in interpersonal communication between students who have a boyfriend with students who do not have a boyfriend at MAN 1 Medan. The hypothesis proposed is that there is no difference of interpersonal communication between students who have boyfriend with students who do not have boyfriend at MAN 1 Medan. Research subjects amounted to 50 students who have been selected based on the criteria required by researchers. The data were collected using interpersonal communication scale by giving questionnaire to the research sample. Data analysis method used in this research is regression test using Pearson Product Moment and Alpha Cronbach formula. Good and quality communication can help improve relationships and overcome problems, whereas poor communication will disrupt those relationships and tends to lead to ongoing conflict. This study aims to determine whether there are differences in interpersonal communication between students who have a boyfriend with students who do not have a boyfriend at MAN 1 Medan. The hypothesis proposed is that there is no difference of interpersonal communication between students who have boyfriend with students who do not have boyfriend at MAN 1 Medan. Research subjects amounted to 50 students who have been selected based on the criteria required by researchers. The data were collected using interpersonal communication scale by giving questionnaire to the research sample. Data analysis method used in this research is regression test using Pearson Product Moment and Alpha Cronbach formula.